Penerapan Metode Evaluation based on Distance from Average Solution (EDAS) Untuk Penentuan Ketua OSIS - Agung Deni Wahyudi (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2022)
The purpose of this study is to apply the EDAS method in the selection of student council presidents using criteria namely academic values, discipline, activeness, responsibility, leadership, organization, and knowledge. So that the results of the application of the EDAS method can be recommendations in making a decision. The application of the EDAS method resulted in candidates for student council president candidates obtained on behalf of Putri with a value of 0.6901 getting 1st rank. 2nd place was obtained by Galih with a value of 0.56805, 3rd place was obtained by Fadli with a value of 0.54785, and 4th place was obtained by Andini with a value of 0.46435.